ANALISIS BUKU TEKS “AKU CINTA BAHASA ARAB 4” KELAS IV KURIKULUM 2013 MADRASAH IBTIDAIYAH KARYA AGUS WAHYUDI (TINJAUAN SEGI KELAYAKAN ISI) - Muhammad Nur Asmawi; Ulfa Djahadi (Program Studi Pendidikan Bahasa Arab (PBA), Fakultas Tarbiyah dan Ilmu Keguruan (FTIK), Instutut Agama Islam Negeri (IAIN) Palu, 2021)
This research is a library research. In collecting research data, the researcher uses documentation techniques. And in analyzing the data, the researcher uses content analysis, where this analysis is used to understand the content and meaning of various studies. Sources of data used are primary data and secondary data. The results of this study indicate that the textbook